2004
DOI: 10.1007/978-3-540-27798-9_7
|View full text |Cite
|
Sign up to set email alerts
|

Large Triangles in the d-Dimensional Unit-Cube

Abstract: Abstract. We consider a variant of Heilbronn's triangle problem by asking for fixed dimension d ≥ 2 for a distribution of n points in the d-dimensional unit-cube [0,1] d such that the minimum (2-dimensional) area of a triangle among these n points is maximal. Denoting this maximum value by Δ of f −line d (n) and Δ on−line d(n) for the off-line and the online situation, respectively, we will show that c1·(log n)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2005
2005
2007
2007

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…With the results from [14], i.e. , using a result of Ajtai, Komlós, Pintz, Spencer and Szemerédi [1] on uncrowded hypergraphs we can improve Theorem 1 slightly (Details are omitted here), namely for fixed integers d, k ≥ 3 and a fixed integer j 0 with 3 ≤ j 0 ≤ d + 1 one can find in polynomial time a configuration of n points in [0,1] d , such that, simultaneously for j = 2, .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With the results from [14], i.e. , using a result of Ajtai, Komlós, Pintz, Spencer and Szemerédi [1] on uncrowded hypergraphs we can improve Theorem 1 slightly (Details are omitted here), namely for fixed integers d, k ≥ 3 and a fixed integer j 0 with 3 ≤ j 0 ≤ d + 1 one can find in polynomial time a configuration of n points in [0,1] d , such that, simultaneously for j = 2, .…”
Section: Discussionmentioning
confidence: 99%
“…Notice that for fixed integers d, j ≥ 2, Theorem 1 yields [14]. Somewhat surprisingly, achieving by a deterministic polynomial time algorithm for the same n points in [0,1] d the lower bound ∆ j,d (n) = Ω(1/n (j−1)/(1+|d−j+1|) ), simultaneously for j = 2, .…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…For k = d, the upper bound in (2) yields the bound from [8] and the lower bound in (1) gives the result from [13]. For k = 2 and any fixed dimension d ≥ 2, the bounds in (1) yield the above mentioned result from [14]. Indeed, our arguments for proving Theorem 1 give a randomized polynomial in n time algorithm, which finds a distribution of n points in [0, 1] d that achieves the lower bound in (1).…”
Section: Introductionmentioning
confidence: 92%
“…Here we consider the following generalization of Heilbronn's problem: given fixed integers d, k with 1 ≤ k ≤ d, find for every integer n ≥ k a distribution of n points in the d-dimensional unit cube [0,1] d such that the minimum volume of a (k + 1)-point simplex arising from these n points is as large as possible. Let 1] d , were given by this author in [14], where it has been shown that c 2,d · (log n)…”
Section: Introductionmentioning
confidence: 99%